Electrostatic Interactions to Attach Latex to Pigment Surface to Reduce Binder Migration - Rao, Pradnya D.; Bousfield, Douglas W.; Tripp, Carl P. (Journal of Coating Science and Technology, 2022)
For many paints, paper coatings, and other pigmented coatings, latex and soluble binders are used to impart mechanical properties. However, non-uniform latex binder distributions are often observed in the thickness direction during application and drying, leading to quality issues. While several publications have documented this issue, few solutions are offered in the literature. Here we report a simple process to use electrostatic interactions to attach latex binder to pigments. Coating suspensions are generated using cationic precipitated calcium carbonate (PCC) pigments that are mixed with anionic styrene-butadiene (SB) latex binders resulting in latex-covered pigments. The migration of latex binder in coatings generated on various substrates under various drying conditions was measured using Raman spectroscopy and compared with reference coatings. The new system shows reduced latex binder migration for most situations than those obtained with the reference coating. The coated papers were also measured for strength, opacity, gloss, water drainage rate, and porosity. Little difference is seen in the picking strength of the coating and gloss compared to coatings prepared with standard formulations. Water drainage rate, opacity, and porosity were higher for latex-covered pigment (LCP) coatings than the reference standard coating; this increased porosity is likely due to the strong electrostatic attraction that exists between the cationic pigment and anionic latex binder that reduces the densification of the coating during drying.